Kabul’s old city: Implications for alternatives to “Western” housing - Watts, Donald J. (King Faisal University, 2009)
This paper presents a new methodology for analyzing and discovering the interactions of social needs and traditional building practices in vernacular Afghan houses. Beginning with identifying common socio-spatial patterns in the traditional Afghan house, this research proceeds to investigate the implications of this traditional building process for planning the housing needs of expanding Afghan cities.
Keywords: Afghanistan; Vernacular architecture; Housing